Theories of the architectural symbolism of the traditional mosque: a preliminary classification - Hazwan Ariff Hakimi; Nik Lukman Nik Ibrahim; Nor Zalina Harun (Penerbit Universiti Kebangsaan Malaysia, 2023)
The productive scholarship on the architectural symbolism of the traditional mosque expounded by the Traditionalist School at the end of the second millennium, which continued well into the third millennium by scholars exhibiting a strong Traditionalist influence or otherwise, is a testament to the subject’s importance to the development of Islāmic architecture. Despite its prolificity and agency, most studies on the subject remain theoretically arbitrary, if not deficient, rudimentary at best, and disjointed. To fill this theoretical gap, this article, for the first time, identifies, outlines, and synthesises the many disparate theories of the architectural symbolism of the traditional mosque to establish a preliminary classification. It employs a hermeneutic reading of 32 significant theoretical and empirical studies on the architectural symbolism of the traditional mosque sourced from books, journals, conference proceedings, and periodicals available to the authors. By capitalising on the textual and comparative analyses, it is found that as many as 28 distinct theories of the architectural symbolism of the traditional mosque with their attendant symbolic dimensions and parameters were posited in all 32 studies, all of which can be consolidated into three broad theoretical frameworks. These findings present an original systematisation of theories of the architectural symbolism of the traditional mosque, which is instrumental in two ways: it encourages scholars to develop existing theories or establish new ones, and it assists Muslims in recognising and acknowledging the spiritual agency of their built forms while offering foreign readers another expansive and inspiring lens to view them.